2022
DOI: 10.1111/jpi.12785
|View full text |Cite
|
Sign up to set email alerts
|

No association between a common type 2 diabetes risk gene variant in the melatonin receptor gene (MTNR1B) and mortality among type 2 diabetes patients

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri butio n-NonCo mmerc ial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…Moreover, although the frequency of the CTT haplotype was significantly different between the MI patient group and the control group in the present study, this difference was no longer significant after correction for multiple testing. Similarly, a study by Xue et al showed that MTNR1B gene variations in patients with diabetes did not increase their risk of CVD mortality [12]. In addition, some of the analyzed cardiovascular risk factors, such as diastolic and systolic blood pressure, BMI, and smoking, were significantly associated with the analyzed polymorphisms in MI patients in this study.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Moreover, although the frequency of the CTT haplotype was significantly different between the MI patient group and the control group in the present study, this difference was no longer significant after correction for multiple testing. Similarly, a study by Xue et al showed that MTNR1B gene variations in patients with diabetes did not increase their risk of CVD mortality [12]. In addition, some of the analyzed cardiovascular risk factors, such as diastolic and systolic blood pressure, BMI, and smoking, were significantly associated with the analyzed polymorphisms in MI patients in this study.…”
Section: Discussionsupporting
confidence: 78%
“…Melatonin action involves the activation of a high-affinity membrane receptor, melatonin receptor 1B [3], encoded by the MTNR1B gene [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seventh, we excluded events that occurred within one year of follow-up. In addition, we performed analyses by censoring up to 31 Dec 2019 (the start of the COVID-19 pandemic 47 ). Finally, we repeated the analyses among those with ≥6 days of accelerometer wear.…”
Section: Methodsmentioning
confidence: 99%
“…Regarding clinical endpoints, individuals with T2DM possessing the MTNR1B gene variant had a greater incidence of myocardial infarction in an analysis of the UK Biobank cohort with a 6.8-year follow-up [64]. In contrast, no associations with mortality have been found [65].…”
Section: Mt and Glucose Homeostasismentioning
confidence: 99%